Model Pembelajaran PjBL untuk Meningkatkan Hasil Belajar Materi Rotasi Bumi bagi Peserta Didik Tunagrahita - Siregar, Astri Akmalia; Nurhastuti, Nurhastuti; Agusta, Rini (Jurnal Penelitian Pendidikan Khusus, 2023)
This research is an action research conducted in two cycles, with 6 participants who are students with intellectual disabilities in the 11th grade at SLB Negeri 1 Padang. The purpose of this study is to improve the learning process and outcomes of students with intellectual disabilities in the subject of Science, specifically on the topic of Earth rotation, through the implementation of project-based learning (PjBL) model. The data collection methods used in this study were tests and observations. The instruments used to collect cognitive data were objective tests, affective domain data were collected using observation sheets, and psychomotor data were collected through performance and product demonstrations. The data obtained were then analyzed using quantitative descriptive analysis techniques. The results of this study indicate that there was an improvement in the learning process and outcomes of the students from pre-cycle with an average score of 30, to cycle I with a score of 60, and cycle II with a score of 81.6, achieving a 100% mastery level. The conclusion of this study is that learning with the PjBL model can enhance the learning process and outcomes.